89.1k views
2 votes
The system of equations Y equals -1/5 X -6 and Y equals negative 2X +3 is shown on the graph below

User MathewS
by
5.3k points

1 Answer

6 votes

Answer:

The solution of the system is (5, -7)

Explanation:

Here we have the system:

y = (-1/5)*x - 6

y = -2*x + 3

We know that this system is graphed below, and the question is incomplete, but I assume that we want to find the solution to this system. If you can see the graph, the solution is just the point where both graphs intersect, but we can find the solution analytically.

We know that:

y = (-1/5)*x - 6

y = -2*x + 3

Then, we can write:

y = (-1/5)*x - 6 = y = -2*x + 3

This leads to:

(-1/5)*x - 6 = -2*x + 3

Now we can solve this for x.

(-1/5)*x + 2*x = 3 + 6

(-1/5)*x + (10/5)*x = 9

(9/5)*x = 9

x = (5/9)*9 = 5

x = 5

now that we know the value of x, we can input this in one of the two equations above to find the correspondent value of y, we will get:

y = -2*x + 3 = -2*5 + 3

y = -10 + 3 = -7

y = -7

Then the solution is:

x = 5 and y = -7, or (5, -7)

User Tony Bao
by
5.1k points